Agglomeration, pollution, and migration: A substantial link, and policy design - Oded Stark; Yu Pang; Simon Chengze Fan (University of Bonn, Center for Development Research (ZEF), 2022)
We study a developing countries setting in which agglomeration efficiency of urban production attracts rural-to-urban migration, whereas urban pollution deters rural-to-urban migration. By means of a general equilibrium model we study the formation of policies aimed at striking a socially optimal balance between supporting efficient levels of urban agglomeration and mitigating urban pollution in the presence of endogenous rural-to-urban migration. We show that without government intervention, although rural-to-urban migration contributes to agglomeration economies, it does not improve social welfare because it also exacerbates environmental degradation. We also show that urban pollution problems cannot be resolved by means of environmental regulation alone: for example, an emissions tax aimed at curbing urban pollution can backfire as and when it increases the appeal of rural-to-urban migration. A policy of emissions tax in conjunction with a subsidy to rural individuals is an effective means of enhancing urban productivity while reducing urban pollution.
Keywords: H23; J61; O15; R23; 330; Rural-to-urban migration; Industrial emissions; Polluting urban agglomeration; Environmental regulation; Policy formation